An Analysis Of Internal Control System Of Merchandise Inventory At Toko Saga Motor Panorama In Bengkulu City - Titin Dwi Jayanti; Karona Cahya Susena; Wagini Wagini (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2023)
This study aims is to find out whether the analysis of the internal control system for merchandise inventory at Toko Saga Motor Panorama in Bengkulu City is in accordance with the control system according to Mulyadi (2016: 488). The theory associated with the title explained is the internal assessment system. Toko Saga Motor Panorama in Bengkulu City, carries out cash and credit sales as an effort to attract as many customers as possible to Toko Saga Motor Panorama in Bengkulu City. This research is a type of descriptive research. The data collection method was carried out by observation, interviews and documentation obtained Toko Saga Motor Panorama in Bengkulu City. The results of this research show that the internal assessment system for merchandise inventory at Toko Saga Motor Panorama in Bengkulu City is not in accordance with the control system according to Mulyadi (2016: 488) so it can be said that it has not been carried out effectively. This can be seen from Toko Saga Motor Panorama in Bengkulu City which does not have its own control system and does not have adequate storage and there are no operations in the organizational structure at Toko Saga Motor Panorama in Bengkulu City because it is only carried out by two people who run all the divisions. In determining the inventory valuation method, the company uses the LIFO method because the last item will be the cost of goods sold. This will provide greater profits compared to the FIFO method.